Physicochemical and Sensory Properties of Pineapple Juice Incorporated with Herbs - Tokiman, Nur Jannah; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2024)
Malaysia contains a diverse range of crops, encompassing fruits, vegetables, and several types of herbs. Through the efficient utilization of the earth's resources, we can attain significant benefits for ourselves, society, and the environment. Pineapple is classified as a tropical fruit, along with mango, papaya, and avocado. The popularity of fresh pineapple juice stems from its delectable flavor, enticing aroma, and several beneficial attributes. Pineapple is a rich source of vitamin C and has a high nutritional value. However, in Malaysia it is not very popular to combine pineapple juice with some types of herbs. The study aims to develop pineapple juice with herbal extract, evaluate consumer acceptance and determine physicochemical analyses of the acceptance product. The consumer acceptance was evaluated based on color, aroma, sweetness, sourness, aftertaste and overall acceptance using 5-hedonic scale. The physicochemical analyses on pH value, TSS and color were highlighted. For sensory evaluation, pineapple juice added dates (4.12) and pineapple juice added with mint (3.46) were preferred by the panelist. The range for pH of pineapple juice between 3.91 to 3.45. The physicochemical analyses was in optimum value except for TSS value. Thus, pineapple juice added with herbs has the potential to be health beverage.